Thematic studies, c790-present day - Bruce, Lindsay; Cloake, Jon A.; Newman, Kevin; Wilkes, Aaron (Oxford AQA GCSE history, 2016)
Thematic Studies c790-Present Day (Britain: Health, Power, and Empire and Migration) is part of a brand new series written specially to match the new 2016 AQA GCSE History specification, and is developed by an expert team led by an experienced head of history and an author with senior examining experience. This combined British Thematic Studies Book covers developments of each Thematic Study in Britain over a long period of time, and considers the causes, scale, nature, impact and consequences of short and long term developments. Carefully selected Sources allow students the opportunity to analyse and evaluate primary sources in context. Practice Questions and Study Tips help students prepare for the new AQA exam questions, and features such as Extension, Over to you and How to provide step-by-step explanations of how to put into practice essential history skills such as analysing an interpretation, cartoon or essay writing.